Effects of pregnancy on cardiac structure and function in women with sickle cell anemia: a longitudinal comparative study. (12th December 2022) - Aliyu, Zubaida; Kushimo, Oyewole A.; Oluwole, Ayodeji A.; Amadi, Casmir; Oyeyemi, Nuvie; Mbakwem, Amam; Afolabi, Bosede B.
Abstract: Background: Sickle cell anemia is the commonest hemoglobinopathy in pregnant Nigerian women, and cardiac manifestations are a significant feature of the disease especially in pregnancy. Pregnant women with sickle cell anemia are at high risk of morbidity and mortality and cardiac dysfunction in them increases this risk and may compromise their post-partum health. Objective: To evaluate the cardiac size and function in women with sickle cell anemia (HbSS) during late pregnancy and postpartum. Methodology: This was a longitudinal comparative study in which 40 women, consisting of 20 pregnant HBSS and 20 pregnant HBAA women controls, were recruited. Echocardiography was performed in the third trimester of pregnancy and 6 weeks postpartum. Results: There was a decrease in the mean left atrial diameter ( p < .001), left ventricular diameter in diastole ( p = .041), and left ventricular mass ( p = .004) of HBSS women in the postpartum period compared to their antepartum state. In contrast, there was no significant difference in most cardiac dimensions of pregnant vs postpartum HBAA women. There was no significant change in cardiac function in the pregnant vs postpartum states in both study groups. There were significant differences in cardiac size but not function when comparing HBSS and HBAA women in pregnancy and postpartum. Conclusion: Changes in cardiac size of sickle cell women in pregnancy does not appear to affect cardiac function during pregnancy and in the puerperium, suggesting that the increased size may purely be a response to their chronic anemic state. Studies following women up for longer periods including those with co-morbidities are recommended